Pengaruh Pemberian Ekstrak Daun Nimba (Azadiractha indica A.Juss) Sebagai Pestisida Nabati Terhadap Hama Helopeltis antonii Pada Tanaman Kakao (Theobroma cacao L.) Di Desa Hebing Kecamatan Mapitara - Maria Yuniati; Rofinus Galis; Mariana Sada (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the effect of giving neem leaf extract (Azadirachta indica A. Juss) as a vegetable pesticide against Helopeltis antonii pests on cocoa plants (Theobroma cacao L.). This research was conducted in Hebing Village, Mapitara District, Sikka Regency, which lasted for one month, from March 1 to March 31, 2023. The research method used was an experimental method with a Randomized Block Design (RBD). The factor studied was the effect of neem leaf extract on the number of punctures by Helopeltis antonii on cocoa pods, which consisted of 5 treatments and 4 replications. The treatments used in this study were P0: Without neem leaf extract (control), P1: 30ml neem leaf extract, P2: 60ml neem leaf extract, P3:90ml neem leaf extract, and P4: 150ml neem leaf extract. The parameter measured was the number of punctures by Helopeltis antonii. Research data were analyzed by normality test and homogeneity test. The normality test shows that the significance value is 0.200, which is a significant value > 0.05, meaning that the data is declared normal. The homogeneity test shows a significance value of 0.372, which is a significant value > 0.05 so the data is declared homogeneous. Based on the results of the ANOVA test, it was concluded that the administration of neem leaf extract affected the number of Helopeltis antonii pest pricks between treatments.